Efficient cadmium removal from industrial wastewater generated from smelter using chemical precipitation and oxidation assistance - Lee, Yeon Jin; Lee, Chang Gu; Min, Kyung Jin; Park, Seong Jik (Water Environment Research, 2024)
The effective treatment of cadmium (Cd) in smelting wastewater is of great industrial importance. This study investigates the efficient removal of Cd from real industrial smelting wastewater via chemical precipitation using a series of experiments. In particular, the effects of different precipitants, agitation conditions, and the addition of NaOCl on Cd removal and pH variation are investigated. CaO (3.75 g/L), NaOH (3.50 g/L), and Ca(OH)2 (3.75 g/L) are found to be effective in elevating the wastewater pH and achieving high Cd removal rates (>99.9%), while the use of NaOH as a precipitant maintains a high Cd removal rate even at low agitation intensities. The properties of the produced sludge and supernatant are also determined using moisture content, particle size, and sludge leaching analyses due to the importance of economic and environmental sustainability in filtration, dewatering, and waste disposal processes. In addition, the addition of 2% NaOCl is tested, revealing that it can improve the Cd removal efficiency of Ca(OH)2, thus potentially reducing processing costs and enhancing the environmental benefits. Overall, these findings offer valuable insights into the removal of Cd from smelting wastewater, with potential implications for both environmental sustainability and economic viability. Practitioner Points: CaO, NaOH, and Ca(OH)2 effectively remove Cd (>99.9%) from smelting wastewater. The use of NaOH leads to high Cd removal rates even at low agitation speeds. Adding 2% NaOCl can reduce the Ca(OH)2 dose for more economical Cd removal.
Keywords: Cadmium removal; Chemical precipitation; Dosage; Environmental sustainability; Industrial wastewaters; Leaching test; Precipitant; Removal rate; Smelter; Smelting wastewaters; Cadmium; Calcium Hydroxide; Chemical Precipitation; Hydrogen-Ion Concentration; Industrial Waste; Oxidation-Reduction; Waste Disposal, Fluid; Wastewater; Water Pollutants, Chemical; Water Purification; dosage; industrial wastewater; leaching test; precipitant; smelter